PENDAMPINGAN PELATIHAN PENGGUNAAN WEBSITE SIABDES DI BUMDES KARYA MUKTI - Pringgabayu, Dematria; Rubiyanti, Nurafni; Fakhri, Mahendra (Jurnal Pengabdian Kepada Masyarakat, 2025)
BUMDES is basically a business entity formed to optimize village potential and empower village communities. BUMDES is a very ideal business model. In practice, BUMDES still has several weaknesses, including communication between BUMDES and village community business actors, very new system management, manual system implementation, no joint commitment from BUMDES managers, no understanding with village communities regarding BUMDES programs, low public trust in BUMDES performance, low manager innovation, poor governance, supply chain problems, and community recognition. The purpose of this community service activity in general is to build partnership synergy as a manifestation of the vision and mission of Telkom University. Specifically, the purpose of this community service is to develop accounting and financial systems, design business governance and business processes, prepare business plans, prepare marketing plans, and supply chains, and digitalization that can be used by BUMDES Karya Mukti located in Tasikmalaya Regency. The output of community service activities carried out includes training/technical guidance (bimtek), creation of system/process prototypes, standard operating documents, and the formation/strengthening of national and regional Asian business networks.